PPARγ1 and LXRα face a new regulator of macrophage cholesterol homeostasis and inflammatory responsiveness, AEBP1 - Majdalawieh, Amin (2010)
Peroxisome proliferator-activated receptor γ1 (PPARγ1) and liver X receptor α (LXRα) are nuclear receptors that play pivotal roles in macrophage cholesterol homeostasis and inflammation; key biological processes in atherogenesis. The activation of PPARγ1 and LXRα by natural or synthetic ligands results in the transactivation of ABCA1, ABCG1, and ApoE; integral players in cholesterol efflux and reverse cholesterol transport. In this review, we describe the structure, isoforms, expression pattern, and functional specificity of PPARs and LXRs. Control of PPARs and LXRs transcriptional activity by coactivators and corepressors is also highlighted. The specific roles that PPARγ1 and LXRα play in inducing macrophage cholesterol efflux mediators and antagonizing macrophage inflammatory responsiveness are summarized. Finally, this review focuses on the recently reported regulatory functions that adipocyte enhancer-binding protein 1 (AEBP1) exerts on PPARγ1 and LXRα transcriptional activity in the context of macrophage cholesterol homeostasis and inflammation.